Northern Exposures: A Canadian Perspective on Occupational Health and Environment - Bennett, David (Work, health, and environment series, 2010)
David Bennett is the retired National Director of Health, Safety and Environment of the Canadian Labour Congress and the Book Review Editor of the journal New Solutions. Northern Exposures is the result of thirty years of work in the labor movement on workplace health and safety and environmental protection. In the 1990s, the author had a central responsibility in moving the Canadian Labour Congress from its established work in health and safety into environmental protection, a story detailed in Northern Exposures. The book is a collection of published articles and reviews, linked by a new Introduction that shows the development of the thinking and actions of the Canadian labor movement in areas that were in constant flux. --Publisher's description. Contents: The right to know about chemical hazards in Canada,1982-2006 -- Labour and the environment at the Canadian Labour Congress: the story of the convergence -- Occupational health: a discipline out of focus -- Pesticide reduction: a case study from Canada -- The Canadian Labour Congress' pollution prevention strategy -- Prevention and transition -- Cancer battles and the sleep of reason policy and science need not be related: review -- Book about cancer: pragmatic purpose, profound analysis: reviews -- The secret history of the war on cancer: review -- Industrial materials: a guidebook for the future: review -- 'Natural capitalism's' bold theory: review -- Beware ISO -- ISO and the WTO: a report to the International Confederation of Free Trade Unions' Working Party on Health, Safety, and Environment -- Health and safety management systems: liability or asset?
Keywords: Canada; Environmental health; Industrial hygiene; Occupational health and safety; Public Policy